Urban tissue transformation under the densification policy: The case of Oslo - Zurovac, Gordana (FormAkademisk, 2020)
Based on the case of Oslo, this paper focuses on the physical results of the implementation of the densification policy in Norway. By applying the urban morphological approach, the paper examines transformation of urban tissue at the intermediate spatial scale (buildings – plot – street – urban block). It covers 71 cases of multi-family residential buildings and analyses the pre-existing tissues where they occur as well as the principles of intervention. The results reveal a myriad of tissue types (mixed tissues being dominant) and a significant number of entirely new urban blocks. Tissues are investigated in terms of conditions and challenges, and new blocks are analysed for their morphological characteristics and application in densification.